Financial toxicity in cancer patients and subsequent risk of repeat acute care utilization - Shi, Julia J.; Maldonado, J. Alberto; Wu, Chi-Fang; Peterson, Susan K.; Chen, Ying-Shiuan; Diao, Kevin; Volk, Robert J.; Giordano, Sharon H.; Shih, Ya-Chen T.; Kaiser, Kelsey; Smith, Grace L. (Frontiers in Psychology, 2023)
Background. Acute care (AC) visits by cancer patients are costly sources of healthcare resources and can exert financial burden of oncology care both for individuals with cancer and healthcare systems. We sought to identify whether cancer patients who reported more severe initial financial toxicity (FT) burdens shouldered excess risks for acute care utilization. Methods. In 225 adult patients participating in the Economic Strain and Resilience in Cancer (ENRICh) survey study of individuals receiving ambulatory cancer care between March-September 2019, we measured baseline FT (multidimensional score 0-10 indicating the least to most severe global, material, and coping FT burdens). All AC visits, including emergency department (ED) and unplanned hospital admissions, within one-year follow-up were identified. The association between severity of FT and the total number of AC visits was tested using Poisson regression models. Results. A total of 18.6% (n=42) of patients had any AC visit, comprised of 64.3% hospital admissions and 35.7% ED visits. Global FT burden was associated with the risk of repeat AC visits within one-year follow-up (RR= 1.17, 95% CI 1.07-1.29, P<0.001 for every unit increase), even after adjusting for sociodemographic and disease covariates. When examining subdimensions of FT, the burden of depleted FT coping resources (coping FT) was strongly associated with risk of repeat AC visits (RR= 1.27, 95% CI 1.15-1.40, P<0.001) while material FT burden showed a trend toward association (RR= 1.07, 95% CI 0.99-1.15, P = 0.07).In this prospective study of acute oncology care utilization outcomes among adult cancer patients, FT was a predictor of a higher burden of acute care visits. Patients with severely depleted material, practical, and social coping resources were at particular risk for repeat visits. Future studies are needed to identify whether early FT screening and intervention efforts may help to mitigate urgent acute care utilization burdens.